2017
DOI: 10.1002/pola.28871
|View full text |Cite
|
Sign up to set email alerts
|

Visible light‐emitting diode‐sensitive thioxanthone derivatives used in versatile photoinitiating systems for photopolymerizations

Abstract: Novel thioxanthone (TX) derivatives are used as versatile photoinitiators upon visible light-emitting diode (LED; e.g., 405, 425, and 450 nm) exposure. The mechanisms for the photochemical generation of reactive species (i.e., cations and free radicals) produced from photoinitiating systems based on the photoinitiator and an iodonium salt, tris(trimethylsilyl)silane, or an amine, were studied by UV-vis spectroscopy, fluorescence, cyclic voltammetry, steady-state photolysis, and electron spin resonance spin-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…As shown in Figure c, in the final monomer conversions ( t = 180 s) under different LED irradiation in the PI/MDEA‐containing systems, two PIs exhibited good performance in the near‐UV and visible range (365–475 nm). Thus, an improvement in long‐wavelength initiation ability was achieved compared with the commercial type II PI (such as isopropyl thioxanthone), which could not initiate FRP at irradiation wavelengths longer than 450 nm as reported in our previous work (Figure S9). When MO and DO were compared, the results showed that the time to achieve maximum heat release in DO was shorter than that in MO in the PI/MDEA‐containing formulation under all conditions.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…As shown in Figure c, in the final monomer conversions ( t = 180 s) under different LED irradiation in the PI/MDEA‐containing systems, two PIs exhibited good performance in the near‐UV and visible range (365–475 nm). Thus, an improvement in long‐wavelength initiation ability was achieved compared with the commercial type II PI (such as isopropyl thioxanthone), which could not initiate FRP at irradiation wavelengths longer than 450 nm as reported in our previous work (Figure S9). When MO and DO were compared, the results showed that the time to achieve maximum heat release in DO was shorter than that in MO in the PI/MDEA‐containing formulation under all conditions.…”
Section: Resultsmentioning
confidence: 58%
“…1 H NMR and 13 C NMR spectra were recorded on a Bruker 400 M NMR spectrometer with CDCl 3 as the solvent and chemical shifts were reported in parts per million (ppm), downfield from the Me 4 Si resonance, which was used as the internal standard. Mass spectra were recorded on a Micromass GCT and Micromass GCTTM . All related spectra were shown in Data S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of these onecomponent photoinitiators was based on the functionalisation of thioxanthone with a coinitiator moiety (hydrogen donor). Wu et al 21…”
Section: Introductionmentioning
confidence: 99%
“…Now, the commercial PAGs exhibit weak spectral sensitivity at long wavelengths ( λ abs > 320 nm), which limit their applications of new light sources, for example, light‐emitting diodes (LEDs) . PAGs have been adapted to operate under LED irradiation, especially near‐UV/visible LEDs . These eco‐friendly light sources have the advantages of low cost, absence of harmful ultraviolet light, high efficiency, and so on …”
Section: Introductionmentioning
confidence: 99%